Estimates and prevention of Crimean-Congo hemorrhagic fever risks for health-care workers - (:unkn) unknown (Springer Netherlands, 2007)
Crimean-Congo hemorrhagic fever virus (CCHFV) is one of the most widespread pathogens causing viral hemorrhagic fever (VHF). A disease with the clinical and epidemiological features of Crimean-Congo hemorrhagic fever (CCHF) has been long known in Central Asia, its first known formal description appearing in a text written circa 1110 in what is now Tadjikistan [43]. It has caused outbreaks in dry steppe, savannah, semidesert and foothill areas of Eastern and Central Europe, most of European and Asian parts of the former USSR, parts of the oriental region, and in Africa from Egypt to South Africa and from Senegal to Kenya. Within 25 years of its first detailed description of clinical and epidemiological features in the Ukraine, the long-known hemorrhagic fever had been described extensively, the causative agent had been isolated and shown to replicate the disease in nonimmune humans, an animal model, and a diagnostic test was developed which showed its area of prevalence. Although CCHFV infection is rarely documented in humans, outbreaks continue to occur and are on the rise in Turkey. But what are the risks of secondary transmission to health-care workers (HCW)? © 2007 Springer Netherlands. All rights reserved.